Kedisiplinan Kerja dan Manajemen Kinerja Salesperson PT Sun Mega Motor Hyundai Yogyakarta - Wirabuana, Atha Aganta; Linando, Jaya Addin (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
The purpose of this research is to understand and improve work discipline and salesperson performance management at PT Sun Mega Motor Hyundai Yogyakarta. The research method employed is qualitative research using primary data obtained through observation and interviews. Narrative analysis is utilized for data analysis. The results of this research indicate several implementations and improvements in discipline and performance management at PT Sun Mega Motor Hyundai Yogyakarta. These include creative ideas and repeated approaches needed for consumer search strategies to obtain marketing area permits in elite housing. Complaint management is carried out through coordination and collaboration to address all customer complaints. Effective collaboration can be achieved through discussions and mutual support. The relevance of cleanliness to psychological aspects can enhance motivation and a sense of ownership in the job. Activity plan responsibilities can be fulfilled by adhering to rules and directives from supervisors. Competence achievement through training enhances knowledge and insights in salesperson, thereby improving soft skills in marketing activities